A worldwide comparison of the management of T1 and T2 anterior floor of the mouth and tongue squamous cell carcinoma: extent of surgical resection and reconstructive measures - Kansy, Julia Katharina; Körsgen, Friederike; Hoffmann, Jürgen (Journal of cranio-maxillofacial surgery, 2017)
Introduction Microvascular surgery following tumor resection has become an important field of oral maxillofacial surgery (OMFS). Following the results on general aspects of current reconstructive practice in German-speaking countries, Europe and worldwide, this paper presents specific concepts for the management of resection and reconstruction of T1/T2 squamous cell carcinoma (SCC) of the anterior floor of the mouth and tongue. Methods The DOESAK questionnaire was distributed in three different phases to a growing number of maxillofacial units worldwide. Within this survey, clinical patient settings were presented to participants and center-specific treatment strategies were evaluated. Results A total of 188 OMFS units from 36 different countries documented their treatment strategies for T1/T2 anterior floor of the mouth squamous cell carcinoma and tongue carcinoma. For floor of mouth carcinoma close to the mandible, a wide variety of concepts are presented: subperiosteal removal of the tumor versus continuity resection of the mandible and reconstruction ranging from locoregional closure to microvascular bony reconstruction. For T2 tongue carcinoma, concepts are more uniform. Conclusion These results demonstrate the lack of evidence and the controversy of different guidelines for the extent of safety margins and underline the crucial need of global prospective randomized trials on this topic to finally obtain evidence for a common guideline based on a strong community of OMFS units.